A simple procedure for the production of large ferromagnetic cobalt nanoparticles - Fuller, Rebecca; Goh, B.; Koutsantonis, G.; Loedolff, M.; Saunders, M.; Woodward, R. (R S C Publications, 2016)
© The Royal Society of Chemistry 2016. Epsilon cobalt (ε-Co) nanoparticles in a number of octahedral morphologies have been synthesised. The particles are polycrystalline, with sizes in the order of 30 nm. Magnetic studies reveal the particles are ferromagnetic, with a room temperature saturation magnetisation of 131 emu g -1 . Unlike other large cubic ε-Co syntheses, we have not added an additional co-surfactant. Instead, we have modified the heating regime and reaction agitation. This alternative method highlights the complex chemistry associated with the formation of cobalt nanoparticles by thermal decomposition.